1995
DOI: 10.1128/jvi.69.10.6605-6608.1995
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of vaccinia virus lacking the E3L gene by mutants of E3L

Abstract: Vaccinia virus with the E3L gene deleted was able to replicate in RK-13 but not HeLa cells. This host range phenotype could be complemented by an E3L gene expressed transiently from a plasmid. Analysis of mutants of E3L indicates that the ability to complement deletion of E3L correlates with the ability of mutated proteins to bind double-stranded RNA but not with their ability to migrate to the nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…Poxviruses, including VACV, encode numerous proteins that protect against a variety of innate defenses including those triggered by dsRNA (8)(9)(10). The VACV E3 dsRNA binding protein plays an important role: mutations in the C-terminal dsRNA binding domain result in increased interferon sensitivity and a severe host range defect involving activation of PKR, RNase L, and interferon regulatory factor 3 (IRF3) (11)(12)(13)(14)(15)(16)(17). Roles of PKR and RNase L pathways were suggested by partially restoring replication of a VACV E3 deletion mutant in PKR-or RNase L-deficient mouse embryo fibroblasts (16).…”
mentioning
confidence: 99%
“…Poxviruses, including VACV, encode numerous proteins that protect against a variety of innate defenses including those triggered by dsRNA (8)(9)(10). The VACV E3 dsRNA binding protein plays an important role: mutations in the C-terminal dsRNA binding domain result in increased interferon sensitivity and a severe host range defect involving activation of PKR, RNase L, and interferon regulatory factor 3 (IRF3) (11)(12)(13)(14)(15)(16)(17). Roles of PKR and RNase L pathways were suggested by partially restoring replication of a VACV E3 deletion mutant in PKR-or RNase L-deficient mouse embryo fibroblasts (16).…”
mentioning
confidence: 99%
“…20 Both plants and animals produce a number of these viral suppressors, adding support to the evolved antiviral nature of RNA silencing. 3,21,22 Furthermore, plants that have defective RNA silencing pathways are susceptible to certain viruses. 22 Since its discovery in animal systems, the dsRNA-activated arm of antiviral immunity that degrades a specific gene has been successfully exploited with the use of RNAi.…”
Section: Dsrna and Gene Silencingmentioning
confidence: 99%
“…The vaccinia virus-encoded E3 protein mitigates the antiviral effects of interferon by blocking cellular response pathways dependent on double-stranded (ds) RNA (2,4,21). Genetic and biochemical experiments suggest that the biological activity of E3 derives primarily, if not exclusively, from its capacity to bind to dsRNA (4,5,6,21). The C-terminal half of the 190-amino-acid E3 polypeptide is sufficient to bind dsRNA in vitro (4,22).…”
mentioning
confidence: 99%
“…To better understand the basis for dsRNA recognition by the vaccinia virus E3 protein, we have examined the effects of single-amino-acid substitutions within the dsRBM on RNA binding. Our work builds on that of Jacobs and coworkers, who defined E3 as the virus-encoded inhibitor of PKR, localized its dsRNA binding function to the C-terminal half, and showed that alterations at selected residues within the conserved dsRBM could affect dsRNA binding by E3 protein translated in vitro (4)(5)(6)21). Our approach has been to study the structure and function of the E3 by using purified recombinant protein.…”
mentioning
confidence: 99%